If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 1 + -7x + -5x Combine like terms: -7x + -5x = -12x 13 = 1 + -12x Solving 13 = 1 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 13 + 12x = 1 + -12x + 12x Combine like terms: -12x + 12x = 0 13 + 12x = 1 + 0 13 + 12x = 1 Add '-13' to each side of the equation. 13 + -13 + 12x = 1 + -13 Combine like terms: 13 + -13 = 0 0 + 12x = 1 + -13 12x = 1 + -13 Combine like terms: 1 + -13 = -12 12x = -12 Divide each side by '12'. x = -1 Simplifying x = -1
| X^2-15x-1000=0 | | (7y+x)=4 | | y=3x^3+27x^2 | | 8(x+4)=7(2x+3) | | 5(x-4)-3(x-2)=12 | | 2a-17=21 | | 0.22(x+9)=0.2x+3.6 | | =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w | | 0=(2x)(3x+1) | | 39.95+.35m=69.70 | | 2x+3x=2x-4 | | -8-(12-16)= | | 7a-(3a-4)=16 | | (-3)(2)(-1)(-3)= | | 6-c=16 | | -f+300=-65 | | x^2+3xy-8x-4y= | | 14(b-955)=616 | | F(10)=2x+5 | | 3+-7=4t+7 | | 2m-1=-6m+8 | | -2+10m-10=8(3m+4)-2 | | 49=3(x-3)+4x-1+2x+5 | | 24k=8(x+6) | | 3t^2-20t=-12 | | n=18+m | | 8.25c+12(55-c)=585 | | -5=7+3y | | 6x-13=83 | | 3+-7=4(t+7) | | x^2+x+120=0 |